(untitled) (International Journal of Food and Nutritional Sciences, 2022)
For seat frames, railings, and other vertically supporting components, modern passenger automobiles use carbon steel pipes. The passenger’s clothing and skin could be harmed by rust and abrasion, which are prevented by the nickel coating on these pipes. In spite of this, frequent handling is causing the nickel covering to erode, leaving the pipe vulnerable to oxidation. Pipes need to be replaced frequently to avoid passenger problems. Seeing the coach builders at work, it was decided to find a different and durable solution to the aforementioned problems. Aluminium alloy was found to be a suitable replacement after a thorough review of the literature Additionally, it was noted that the sand casting process of zinc alloyed with aluminium is demonstrating improved tensile strength, bending strength, hardness, and cost aspect. In order to create two distinct alloys, ZA25 and ZA37, by sand casting, testing must be conducted.